Designing a Joyful Mathematical Learning of Fractions using Phet Simulation for Primary School - Zetra Hainul Putra; Jesi Alexander Alim; Arisya Ruspina Putri; Astri Resti Rahmadani; Indah Maslakhatul; Rahmadhani Fitri; Yahya Gunawan; Mohd Ridhuan Mohd Jamil (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Abstract. This study aims to find out the effectiveness of using PhET Simulation learning media. This research uses the Research & Development method (R&D), and the model used is the 4D development model. The 4D model has 4 stages of development, consisting of the definition stage, design stage, development stage and disseminate stage. The research instrument uses observation, evaluation and reflection. The subjects in this research were 20 fourth grade students from a public elementary school in Pekanbaru. The results of this study show that students have an interest in the learning process and they also feel challenged. Using PhET Simulation can also provide experience for them, where this media provides concrete visualization so that students can understand well, especially the fraction material in elementary school.